Assessing the perception of Parkinson’s disease in Al-Ahsa, Saudi Arabia among the visitors of a public campaign: before and after survey - Alokley, Alia A.; Alhubail, Fatimah M.; Al Omair, Abdullah M.; Alturki, Rawan A.; Alhaddad, Rabab M.; Al Mousa, Ali M.; Busbait, Sarah A.; Alnaim, Mohammed A. (Frontiers in Neurology, 2024)
Introduction Insufficient knowledge and beliefs hinder the early diagnosis and provision of adequate treatment and care for PD patients, causing socio-economic burdens. Raising public awareness and understanding the knowledge gap is crucial for effective educational programs and early detection. This study aims to assess the perception of Parkinson’s disease (PD) among visitors of a public campaign conducted to raise PD awareness and knowledge to facilitate early detection and management. Methods A before-and-after study was conducted from May to June 2023, to assess the perception of PD among a public PD campaign visitors in Al-Ahsa, Saudi Arabia. The campaign included educational booths discussing PD symptoms, causes, diagnosis, management, and support. Participants completed a self-administered online questionnaire before and after the campaign. The data were analyzed using SPSS. Results The study included 48 eligible individuals. The mean knowledge score was significantly enhanced following the campaign, rising from 12 to 17.77 points (p < 0.05). The symptoms of PD that showed a significant difference were slow movement, tremors, depression, memory problems, and sleep problems. The campaign had a beneficial effect on participants’ general understanding of PD. Discussion The study showed that public awareness campaigns successfully raised community awareness of PD. Participants’ knowledge improved after the campaign, highlighting its positive effect. Further research could explore measuring the continuity of awareness over a longer period and its impact on improving patients’ lives and could expand the sample size.